Postoperative changes of morphological condition of muscle tissue after surgical treatment in patients with chronic critical lower limb ischemia. - Shkuropat, V. M.; Tverdokhlib, I. V.; Drjuk, M. F. (Морфологія / Morphologia / Morfologìâ, 2011)
The purpose of research was the morphological analysis of anterior tibial muscle after direct, indirect and composite revascularization in near-term and long-term postoperative periods. Patients have been divided into three groups: 1) 37 patients after femoral-tibial reconstruction; 2) 57 patients after indirect revascularisation with autotransplantation of bone marrow; 3) 50 patients after composite revascularization. The observation was carried out in the near-term postoperative period and in 2 years. Studies have shown that the developed method of composite limb revascularization and indications for its use provides a normalizing effect on the early data of the investigated morphological criteria after surgery, and it provides stabilization in the late postoperative period, accompanied by a significant increase in the proportion of muscle fibers (18,6-22,5%) and microvessels (on 17,4-28,3%), as well as the numerical density of hemocapillaries (20,6-52,4%). Immunohistochemistry marker expression of VEGF and CD34, as well as histological and ultrastructural analysis showed that the indirect revascularization causes the normalization and stabilization indicators ischemic muscle tissue through initiation of neovasulogenesis, which leads to a statistically significant increase in the packing density of myofibrils (in 19,5-68,7%) and mitochondria (in 25,7-87,4%) in the fibers of the anterior tibial muscle. Developed method for assessing the adequacy of the fibular artery to optimize the choice of method of revascularization with the use of limb reconstructive surgery on the arteries, or in combination with indirect revascularization by the use of autologous bone marrow aspirate.